Ru-90@bio-MOF-1: A ruthenium(II) metallodrug occluded in porous Zn-based MOF as a strategy to develop anticancer agents - Marson Armando, Renan Augusto [UNESP]; Abuçafy, Marina Paiva [UNESP]; Graminha, Angelica Ellen; Silva, Roberto Santana da; Frem, Regina Célia Galvão [UNESP] (Elsevier, 2021)
One of the major challenges in the field of biomedicine is to use biocompatible carriers to achieve efficient drug delivery in the body. Most of the existing carriers have shown poor loading and rapid drug release. In this context, a subclass of coordination polymers, known as Metal-Organic Frameworks (MOFs), has attracted huge research interest: the unique physical properties of MOFs make them exceptional materials for drug delivery systems. Here, we have synthesized and characterized a non-toxic Zn-based MOF, designated bio-MOF-1, by using 4,4′-biphenyl-dicarboxylic acid and adenine as linkers. The microcrystalline porous material presented great loading capacity (0.340 ​g·g−1) for the antitumoral metallodrug Ru-90 [cis-[Ru(bpy)2(NO2)(solv)](PF6)]. The cellular viability results demonstrated that metallodrug occlusion facilitated its access and increased its availability in the cells. Ru-90 release from bio-MOF-1 depended on pH, so this material is a promising candidate for anticancer drug delivery. Moreover, application of kinetic equation models revealed that the mechanism of Ru-90 release from bio-MOF-1 fitted the Korsmeyer-Peppas model for the system at pH 5.0 and pH 7.4; the plots displayed high linearity and correlation coefficient values (R2) greater than 0.96. The n values were under 0.45 (Korsmeyer-Peppas model), which suggested the quasi Fickian model for the transport mechanism. In conclusion, the kinetic study results showed that bio-MOF-1 delivers the anticancer complex Ru-90 mostly through a diffusive mechanism.
Keywords: Anticancer drugs; Drug delivery systems (DDS); MOFs; Porous zinc(II) coordination solids